2018
DOI: 10.12669/pjms.344.15399
|View full text |Cite
|
Sign up to set email alerts
|

Protein requirement and its intake in subjects with diabetic foot ulcers at a tertiary care hospital

Abstract: Objective:To assess the protein intake and requirement among subject with type 2 diabetes having foot ulcers.Methods:This study was conducted at Baqai Institute of Diabetology & Endocrinology (BIDE), a tertiary care diabetes centre of Karachi, Pakistan among people with type 2 diabetic foot ulcer attending foot clinic from January 2012 to March 2015. The baseline characteristics, dietary intake and laboratory investigations of the study participants were obtained through electronic hospital database “Health Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
1
12
0
5
Order By: Relevance
“…They also had a significantly ( p < 0.05) lower intake of micronutrients such as vitamin E, B1, B2, B3, B6, magnesium, calcium, iron, potassium, and sodium, which are needed for wound healing. Similarly, Sajid et al [ 5 ] showed that protein intake in males and females with DFU was significantly lower than the recommendations (76.9 g and 56.8 g compared to 219.5 g and 130.2 g, respectively). Malnutrition or inadequate intake of essential nutrients involved in wound healing worsens wound severity and increases wound complications such as infection and amputation which may lead to death.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…They also had a significantly ( p < 0.05) lower intake of micronutrients such as vitamin E, B1, B2, B3, B6, magnesium, calcium, iron, potassium, and sodium, which are needed for wound healing. Similarly, Sajid et al [ 5 ] showed that protein intake in males and females with DFU was significantly lower than the recommendations (76.9 g and 56.8 g compared to 219.5 g and 130.2 g, respectively). Malnutrition or inadequate intake of essential nutrients involved in wound healing worsens wound severity and increases wound complications such as infection and amputation which may lead to death.…”
Section: Introductionmentioning
confidence: 94%
“…The rate of major amputations (above the ankle) was almost 11-fold higher in the malnourished group compared to those who were well-nourished (15.5% vs. 1.4%, respectively). Although the high prevalence of malnutrition and its negative effects on the healing of DFU is reported in several studies [ 4 , 5 , 6 , 7 ], to our knowledge there is no study looking at the effects of complete nutrition supplementation. Studies in this field have only examined the effects of supplementing diabetic patients with arginine, glutamine, beta-hydroxy-beta-methylbutyrate (HMB), magnesium, and vitamin E [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa referensi menyatakan bahwa gizi merupakan salah satu faktor yang berperan penting dalam proses penyembuhan luka, karena zat gizi dapat berperan dalam fungsi kekebalan tubuh, sintesis kolagen, dan membangun kekuatan serta kelenturan luka. 11,13 Pada penelitian sebelumnya dinyatakan bahwa pada responden dengan DFU, baik laki-laki maupun perempuan, terdapat ketidakadekuatan asupan protein yang dapat mengganggu proses penyembuhan luka. 13 Konsumsi asupan gizi yang sesuai dapat menunjang penyembuhan DFU.…”
Section: Pendahuluanunclassified
“…The provision of nutritional care is proven to accelerate wound healing. Malnutrition or nutrient deficiencies can impair the maturation phase such as collagen synthesis prolong inflammation, dysfunction of B and T cells due to decrease in phagocytosis, as well as reduce in mechanical strength of the skin (Sajid, Miyan, Zaidi, Jaffri, & Abdeali, 2018;Vas, Edmonds, & Papanas, 2017 GLOBAL JOURNAL OF PUBLIC HEALTH MEDICINE 2021, VOL 3, ISSUE 1 gggggglo…”
Section: Nutrition In Wound Healingmentioning
confidence: 99%
“…Selection of shoes depends on numerous factors; how long someone has had diabetes, the presence of normal sensation on the feet, and if there are any abnormalities or deformities on the feet (O'Brien et al, 2003). Nutrition plays an essential role in the prevention and treatment of DFU, where an inadequate nutrient can result in altered immune function, malnutrition, and poor glycaemic control (Sajid et al, 2018).…”
Section: Wound Size and Gradingmentioning
confidence: 99%